A simple tool to identify elderly patients with a surgically important acute subdural haematoma. Issue 1 (January 2015) - Evans, J.A.; Bailey, M.; Vail, A.; Tyrrell, P.J.; Parry-Jones, A.R.; Patel, H.C.
Abstract: Objectives: ASDH in the elderly is a common and increasing problem, and differs in its pathophysiology from ASDH in younger people. Admitting doctors may have difficulty identifying those elderly patients whose lesions may benefit from surgery. The objective of this study was to determine whether simple neuroradiological measurements could identify those patients, who need urgent neurosurgical referral for consideration for surgery. Design: A retrospective cohort study. Participants: All patients aged 65 years or greater referred to Salford Royal Foundation Trust with the diagnosis of ASDH between 01/01/2008 and 31/12/2011. Methods: The initial presenting CT brain scans were reviewed. The linear dimensions, degree of midline shift and haematoma volume (using ABC/2 method) of all scans were measured and recorded. All presenting radiology was also assessed by a consultant neurosurgeon blind to clinical and CT scan measurement data and patients were categorised as having "surgical" lesions or not. Receiver operating characteristic (ROC) curves were generated and cut point value for 100% sensitivity and specificity were tabled to assess which combination of scan parameters best predicted a "surgical" ASDH. Results: 212/483 patients were considered to have a 'surgical' lesion. All 'surgical' lesions had a volume of >35 ml (range 35–435), maximum thickness of ≥10 mm (range 10–49) and 99% had midline shift ≥1 mm (range 0–32). The best predictor of a 'surgical' lesion was a combination of maximum haematoma thickness and midline shift which offered 100% (95% CI 98.3–100) sensitivity with 83% (95% CI 77.6–87) specificity. Conclusion: Surgically relevant cases of ASDH in the elderly can be reliably and objectively identified by two easily performed scan measurements, haematoma thickness and midline shift. If used in routine practice, these measurements could clarify those patients who may need urgent neurosurgical referral and might avoid unnecessary transfer to neurosurgical units in this cohort.